The Fourth Lateran Council and the Development of Canon Law and the ius commune - Larson, Atria A.; Massironi, Andrea (Brepols, 2019)
This volume collects essays from an international group of scholars who treat various aspects of the Fourth Lateran Council's placement within the development of the <span class=